Osing Kids and the banners of Blambangan; Ethnolinguistic identity and the regional past as ambient themes in an East Javanese town - Arps, Bernard (Wacana, Journal of the Humanities of Indonesia, 2009)
On the basis of the theoretical notions of discursive ambience and ambient discourse, this article examines the recent history of language and ethnicity in Banyuwangi in the far east of Java. Over the last three decades (with roots going back to the 1920s and earlier) a redefinition of the language and culture of the "autochthonous" inhabitants of Banyuwangi has been occurring. Their status and constitution have been changing from a variety of Javanese into an autonomous language and ethnicity, called, after the name given to the language or dialect, Osing. At the same time, an idyllic and heroic picture of the regional past is being constructed and maintained. Prominent among the factors and agencies involved in these two ongoing processes is popular media culture. The regency of Banyuwangi and especially its capital (also named Banyuwangi) are being cast - albeit sporadically and incidentally and sometimes controversially - as an Osing region. At the centre of this historical process, people publicly render themselves - also sporadically and temporarily - Banyuwanginese by listening to and especially by singing, in karaoke-style, a genre of pop music with Osing lyrics and musical characteristics perceived as local.